Transcatheter Closure of Cardiac Defects with Lifetech™ Konar-MultifunctionalOccluder Experience in a Tertiary Care Center - Ara, Andaleeb; Akhtar, Khurram; Mahmood, Amjad; Sadiq, Nadeem; Rafique, Saima; Imtiaz, Sana; Ahmed, Tufail; Akbar, Hajira; Farhan, Mohammad Asad (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the immediate and short-term efficacy and safety of transcatheter closure of cardiac defects with Lifetech™ Konar-MFO in a Tertiary Cardiac Care Center. Study Design: Descriptive cross-sectional study. Setting and Duration of Study: Armed Forces Institute of Cardiology/National Institute of Heart Diseases, Rawalpindi Pakistan, from Mar 2019 to Dec 2021 Methodology: Patients of all ages and both gender undergone transcatheter closure of a cardiac defect with Konar-MFO from Jan 2021 to Dec 2021 were included in the study through non-probability consecutive sampling and approval by the institutional ethical review committee was taken prior to data collection. Data of patients undergone transcatheter closure with Konar-MFO from Mar 2019 to Dec 2020 was extracted retrospectively to assess the immediate and short-term efficacy and safety of the occluder. SPSS version-23 was used for data entry and analysis. Results: A total of 138 patients had transcatheter closure of a cardiac defect with Lifetech™ Konar-MFO during the study period. Case of VSD were 124(89.9%), PDA 9(6.5%), post-operative cases were 4(2.9%) along with 1(0.7%) case of coronary artery fistula (CAF) to the right ventricle. Out of 138 patients, 73(52.9%) were females while 65(47.1%) were males. The mean age was 9.3 ±8.1 years with a range of 6 months to 36 years. Mean fluoroscopy time was 13.68±9.74 min. The procedure was successful in 137(99.27%) cases. The device embolized in 2(1.45%) cases. Conclusion: In selected cases of VSD, PDA and in some post-operative cases the occlusion with Lifetech™ Konar-MFO is safe and efficacious with the added benefits of softness and versatility of the approach.